Deformation response of gradient low-temperature gaseous carburized case in austenitic stainless steel during cyclic nanoindentation. (September 2021) - Liu, Zhe; Wang, Shuaihui; Zhang, Song; Feng, Yajian; Peng, Yawei; Gong, Jianming
Abstract: Low-temperature gaseous carburizing is an effective strengthening technology for austenitic stainless steel which could generate a gradient carburized hardening case on the surface. Cyclic nanoindentation tests with different loadings were carried out to investigate micro deformation response along the depth in the gradient carburized case. The results shows that the properties of carburized case appear a gradient distribution and the elastoplastic property of carburized case is different from that of substrate. Moreover, cyclic hardening occurs during the cyclic nanoindentation tests. The cyclic hardening rate of the carburized case changes along depth and it is significantly higher than that of substrate. The micro morphologies have been scanned and it appears different micro deformation responses along depth in the carburized case during cyclic nanoindentation. Pile-up was found in carburized case but it is not obvious in substrate. Finally, the micro deformation mechanisms of carburized case and substrate during cyclic nanoindentation were analyzed. Backward deviation of hysteresis curve was found in carburized case during cyclic nanoindentation and it is believed that the extremely high compressive residual stress plays a key role in the backward deviation of hysteresis curves for carburized case. Highlights: Deformation responses have been studied and pile-up was found in carburized case but not obvious in substrate. Cyclic hardening rate changes along depth in carburized case and it is significantly higher than that of substrate. Backward deviation of hysteresis curve occurred in carburized case and compressive residual stress plays a key role. The mechanisms of micro deformation response during cyclic nanoindentation were analyzed.